La Peste d’Albert Camus : une analyse de la société coloniale algérienne à travers le prisme de l’épidémie - Berardi, Alessia (Il Tolomeo, 2020)
March 2020: as Coronavirus continues spreading across the globe, the well-known novel La Peste (1947) by Albert Camus appeals to new readers all over the world. This article offers a new modest reading of La Peste by adopting an approach which emerges from the intersection between Environmental Humanities and Postcolonial Studies. We will explore to what extent the plague is an allegory of human suffering and isolate the different levels on which the allegory may work. Furthermore, we will focus on the link between the representation of the plague outbreaking in Oran and the French-Algerian, multiethnic society. What will the ‘epidemic fiction’ reveal about social structures and practices in the context of colonial Algeria’s last years of existence, and how? The representation of the epidemic seems to mirror the inequalities of that colonial society that is not depicted in the novel, and yet it reminds the reader that societies are constructed and, thus, can be improved.